A rare presentation of a patient with COVID-19: Cardiac tamponade - Kemal Emrecan Parsova; Levent Pay; Yusuf Oflu; Ramil Hacıyev; Göksel Çinier (Türk Kardiyoloji Derneği Arşivi, 2020)
The clinical presentation of coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2, can range from only mild, flu-like symptoms to severe progressive pneumonia. Cardiac involvement may be observed during the course of the infection and may include myocarditis, acute myocardial infarction, heart failure, and cardiac rhythm disturbances, but cases describing cardiac tamponade in patients previously diagnosed with COVID-19 are very rare. A 58-year-old female had been hospitalized in another hospital 2 weeks prior to the currently described presentation due to atypical pneumonia. A nasopharyngeal swab specimen was positive for COVID-19. The hospitalization was uncomplicated and she was discharged after a week. She presented at our emergency department with symptoms of shortness of breath and swelling in both legs. A bedside transthoracic echocardiography showed globally depressed left ventricular contraction with an ejection fraction of 30% and there was significant pericardial effusion, which surrounded the entire heart and restricted diastolic filling. The patient was admitted to the coronary intensive care unit with the diagnosis of pericardial tamponade. Bedside pericardiocentesis was performed and serohemorrhagic fluid was drained. Pericardial effusion and pericardial tamponade should be considered in the differential diagnosis of patients with COVID-19 exhibiting dyspnea or worsening of dyspnea. A 58-year-old female has been hospitalized in another hospital two weeks ago due to atypical pneumonia. Her nasopharyngeal swab specimen was positive for COVID-19. She had an uncomplicated course during the hospitalization and was discharged a week ago. She presented to our emergency department (ED) with symptoms of shortness of breath and swelling in both legs. We performed bedside transthoracic echocardiography (TTE) which showed globally depressed left ventricular contraction with ejection fraction (EF) of 30% and there was significant pericardial effusion which surrounded the entire heart and restricted diastolic filling. The patient was admitted to the coronary intensive care unit (CICU) with the diagnosis of pericardial tamponade. Bedside pericardiosentesis was performed and serohemorrhagic fluid was drained. Patients with COVID-19 infection who develops or have worsening dyspnea, pericardial effusion and pericardial tamponade should be considered in differential diagnosis.